Literature, illness, and the family caregiver - Ng, Genevieve Qi Hui (2017)
This thesis looks at the family caregiver and how literature, specifically fictional illness narratives, can complement and add on to existing family caregiver discourse by looking at Kate Clanchy's "The Not-Dead and the Saved" as well as Colm Tóibín's The Blackwater Lightship.